Pyrroloquinoline Quinone Improved Boar Sperm Quality via Maintaining Mitochondrial Function During Cryopreservation - Shanpeng Wang; Qi Wang; Lingjiang Min; Hailiang Cao; Adedeji O. Adetunji; Kaifeng Zhou; Zhendong Zhu (Antioxidants)
Due to oxidative damage and mitochondrial dysfunction, boar semen cryopreservation remains a significant challenge. This study investigates the effects of pyrroloquinoline quinone (PQQ), a mitochondrial-targeted antioxidant, on the post-thaw boar sperm quality during cryopreservation. Boar semen was diluted in a freezing extender containing different concentrations of PQQ (0, 10, 100, 1000, 10,000 nM). After freezing–thawing, the sperm motility, viability, acrosome integrity, mitochondrial activity, adenosine triphosphate (ATP) levels, DNA integrity, malondialdehyde (MDA) levels, reactive oxygen species (ROS) levels, superoxide dismutase (SOD) activity, mitochondrial transcription proteins levels, and fertilization capacity were assessed. The results show that 1000 nM PQQ supplementation to the freezing extender significantly enhanced post-thaw sperm motility, viability, and acrosome integrity compared to the control (p < 0.05). Additionally, 1000 nM PQQ increased mitochondrial membrane potential (MMP) and ATP levels, while decreasing MDA and mitochondrial ROS levels, and reducing DNA damage (p < 0.05). Furthermore, the levels of mitochondrial-encoded proteins were significantly elevated in the 1000 nM PQQ group compared to the control (p < 0.05). Interestingly, sperm in the 1000 nM PQQ group showed a higher binding rate to oviductal epithelial cells and the zona pellucida (ZP), indicating higher fertilization potential. These findings suggest that the use of mitochondria-target antioxidant, PQQ, can improve post-thaw boar sperm quality and fertilization via its capacity to reduce oxidative stress and protect mitochondrial function.